State Responsibility and Corporate Accountability for Transboundary Haze Pollution: a Comparative Analysis Of International and Indonesian Law - Maura Alifia Khairunnisa; Jelly Leviza; Fajar Khaify Rizky (CV. Cognispectra Publishing, 2026)
Transboundary haze pollution from forest and land fires raises two distinct legal questions: when a State may incur international responsibility for harm originating within its territory, and how private corporations responsible for fire-related conduct may be held accountable under domestic law. This study analyzes those questions through a normative juridical method using treaty, statute, conceptual, case, and comparative approaches. The analysis focuses on the ASEAN Agreement on Transboundary Haze Pollution (AATHP), the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA), relevant international jurisprudence, and Indonesia's environmental and plantation laws. The study finds that corporate land burning is not automatically attributable to Indonesia under the law of State responsibility. International responsibility requires an applicable primary obligation, conduct attributable to the State, and a breach of that obligation; in this context, the relevant State conduct may consist of a failure by public authorities to exercise the due diligence required for prevention, supervision, information exchange, cooperation, or enforcement. ARSIWA supplies the secondary rules governing the consequences of an established breach rather than the primary environmental duty itself. The AATHP is a binding regional treaty with substantial preventive and cooperative duties, but its enforcement architecture remains limited because disputes are confined to consultation or negotiation. Indonesian law, by contrast, can impose administrative, civil, and criminal consequences directly on corporations. The article develops a two-layer accountability framework linking international State responsibility with domestic corporate accountability and identifies evidence-sharing, source attribution, and enforcement coordination as the principal interface gaps that must be addressed